Verification of flexural buckling according to Eurocode 3 part 1‐1 using bow imperfections. Issue 4 (November 2016) - Lindner, Joachim; Kuhlmann, Ulrike; Just, Adrian
Abstract: The resistance of compression members may be calculated by the design buckling resistance based on the reduction factorχ, which depends on the slenderness, or by the cross‐section resistance based on internal forces according to a second‐order analysis taking into account equivalent initial bow imperfections as well. The second way is especially advantageous in the case of axial forces and bending. Values for equivalent initial bow imperfections are given in codes such as Eurocode 3 [5] or DIN 18800 [4]. For comparison, initial bow imperfections are derived here from the buckling curves for compression members with different cross‐sections, buckling directions and steel grades based on different types of cross‐sectional interaction. The results are discussed and commented with regard to the design of compression members. Furthermore, investigations are carried out for cases of axial compression and bending moments My or Mz . Data available from ultimate load calculations are used for comparison. The consequences for the assumed design verification according to second‐order theory are discussed and a proposal is presented.